FROM SCREENS TO MINDS: BRAND RECALL’S EFFECT ON VIRTUAL INFLUENCER INSTAGRAM CONTENT - Putri, Angely Olivia; Cokki , Cokki (International Journal of Application on Economics and Business, 2024)
This study aims to examine the effect of product placement on virtual influencer Instagram content towards brand recall of Gucci and Nike. Convenience sampling technique is used to take samples and a total of 308 Tarumanagara University students from 8 faculties were participated as an experiment subjects. The experiment design used in this study is pre-test and post-test without control group. The treatment in this study is virtual influencer Instagram content which concieves product placement. Data collection was carried out in the form of a field experiment, using questionnaires administered directly in the field, and processed using SPSS. The results of hypothesis testing proved significant where product placement on virtual influencers had a positive effect on Gucci brand recall. However, for Nike, the hypothesis did not yield significance. Based on this result, it can be concluded that product placement on virtual influencers does not increase but reinforce Nike brand recall. This study provides theoretical insights that the practice of product placement in virtual influencer Instagram content is successful, which can be practically applied by business owners to integrate product placement and virtual influencers into promotional activities.